2012
DOI: 10.5012/bkcs.2012.33.10.3253
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study on Nucleophilic Substitution Reactions of Phenyl Y-Substituted-Phenyl Carbonates with Z-Substituted-Phenoxides: Effect of Modification of Nonleaving Group from Benzoyl to Phenyloxycarbonyl on Reactivity and Reaction Mechanism

Abstract: Second-order rate constants for the reactions of phenyl Y-substituted-phenyl carbonates 5a-g with Zsubstituted-phenoxides (k Z-PhO −) have been measured spectrophotometrically in 80 mol % H 2 O/20 mol % DMSO at 25.0 ± 0.1 o C. 4-Nitrophenyl phenyl carbonate (5e) is up to 235 times more reactive than 4-nitrophenyl benzoate (4e). The Brønsted-type plot for the reactions of 5e with Z-substituted-phenoxides is linear with β nuc = 0.54, which is typical for reactions reported previously to proceed through a concert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Earlier, Um et al . reported that the β nuc values for the reactions of 4‐nitrophenyl phenylcarbonate and 4‐nitrophenyl benzoate with aryloxides in 20 mol % DMSO(aq) were 0.54 and 0.72, respectively . This outcome has been interpreted with the concerted mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier, Um et al . reported that the β nuc values for the reactions of 4‐nitrophenyl phenylcarbonate and 4‐nitrophenyl benzoate with aryloxides in 20 mol % DMSO(aq) were 0.54 and 0.72, respectively . This outcome has been interpreted with the concerted mechanism.…”
Section: Discussionmentioning
confidence: 92%